2000
DOI: 10.1191/135245800678827851
|View full text |Cite
|
Sign up to set email alerts
|

Apoliprotein E and multiple sclerosis: impact of the epsilon-4 allele on susceptibility, clinical type and progression rate

Abstract: The purpose of this study was to investigate the relation between APOE genotype and Multiple Sclerosis (MS) in a genetically homogeneous population. We examined 240 patients consulting the MS-clinic during a period of 3 years (1996 - 1999). The mean age of the patients was 41.7 years (range 19 - 80 Y, SD 10.0 Y). As a measure of the progression rate (PR) the last registered Expanded Disability Status Scale (EDSS) score was divided by the time span (years) from disease onset until the latest assessment. The APO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
2
6

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 0 publications
5
41
2
6
Order By: Relevance
“…functional polymorphism of the apoe gene would then be expected to affect the long-term outcome. the presence of the apoe * ε4 allele or rather of the ε3/ε4 genotype (the ε4/ε4 genotype is rare) has been suggested as an unfavorable prognostic factor independent of age of onset, gender and duration of disease in different studies (77)(78)(79)(80)(81)(82)(83). However, other studies have not confirmed these findings (84)(85)(86).…”
Section: Apolipoprotein E Gene (Apoe)mentioning
confidence: 38%
“…functional polymorphism of the apoe gene would then be expected to affect the long-term outcome. the presence of the apoe * ε4 allele or rather of the ε3/ε4 genotype (the ε4/ε4 genotype is rare) has been suggested as an unfavorable prognostic factor independent of age of onset, gender and duration of disease in different studies (77)(78)(79)(80)(81)(82)(83). However, other studies have not confirmed these findings (84)(85)(86).…”
Section: Apolipoprotein E Gene (Apoe)mentioning
confidence: 38%
“…In a study in which the frequency of APOE ε4/ε4 homozygotes was significantly higher among MS patients as compared to controls, the APOE ε4/ε4 genotype was associated with increased risk of developing MS (30). The APOE gene consists of multiple alleles, leading to the occurrence of the three common apoE isoforms.…”
Section: Discussionmentioning
confidence: 98%
“…[7][8][9][10][11][12][13][14][15] Specifically, the APOE-4 allele was associated with a more severe disease course, whereas carriers of the APOE-2 allele appeared more likely to have a milder form of MS. However, a similar number of studies failed to replicate this association.…”
Section: Introductionmentioning
confidence: 97%